Identifikasi Literasi Digital Penerapan Pembelajaran Jarak Jauh pada Tingkat Universitas Berbantukan e-LMS di Era 4.0 - Wahyu, Milde; Yakob, Syahmardi; Rasli, Amran (Universitas Batanghari Jambi, 2025)
This research aims to explore the integration of digital literacy in e-LMS-based distance learning at university level in the 4.0 era. This research was conducted at the Open University involving 135 students. This research uses mixed methods. Data collection through interviews and questionnaires. The results show that students have basic skills in using digital technology for learning, especially in using social media platforms and applications such as Google Classroom and Zoom. However, students' abilities in creating digital content and critically evaluating information still need to be improved, such as distinguishing correct information from incorrect and modifying digital resources have not been mastered optimally.